Anal Cancer in HIV Patients - Experience at Hospital de Curry Cabral - Póvoas, Dina; Fernandes, Cândida; Macia, Vasco; Flor de Lima, Bárbara; Rodrigues, Ana; Maltez, Fernando; Cardoso, Jorge (Journal of the Portuguese Society of Dermatology and Venereology, 2016)
Introduction: Men who have sex with men, particularly those infected by human immunodeficiency virus (HIV), have an increased risk of anal cancer. Unlike most opportunistic or AIDS-defining events, data have been contradictory regarding impact of antiretroviral therapy, viral suppression and immunologic reconstitution on HPV infection prevention and related cancers. Vaccination against human papillomavirus (HPV) is presently recommended in all HIV-infected patients, whereas there is still an on-going debate about the need for anal cancer screening programmes. Material and methods: The authors performed a retrospective study of anal cancer cases diagnosed between 2000-2015 in HIV patients on follow up at the Infectious Diseases Unit at Hospital de Curry Cabral, in Lisbon. We present the clinical and epidemiological characteristics of anal cancer cases throughout a fifteen-year period. Results: Anal cancer was diagnosed in ten patients, most of them MSM, HIV-infected for an average time of 15.1 years, with an average TCD4+ cell count of de 441 cells/uL. Anal cancer diagnosis was more frequently performed at stage III and treatment most frequently involved surgery, occasionally with radiotherapy. Four patients died. Conclusion: There is a need for consensual anal cancer screening programs, along with a need to reinforce HPV vaccination in men, particularly men who have sex with men, regardless of HIV infection.